Jokalante CIS e-Learning Module Development Consultation - Hansen, James; Trzaska, Silwia; Kebe, Amy; Seck, Babacar; Fall, Serigne; Thiaw, Moussa; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report summarizes a consultation held in May 2025 between Jokalante, the International Research Institute for Climate and Society (IRI), and ILRI under the AICCRA project, to co-develop an e-learning module on Climate Information Services (CIS) tailored for the Senegalese context. The course aims to strengthen the capacity of agricultural professionals—particularly those with limited formal education—to understand, use, and communicate climate information in support of farmers and pastoralists. The partners agreed to adapt RUFORUM’s “Introduction to Climate Services for Agriculture” curriculum into two versions: a free-access format and a paid, certificate-based version with competency assessments. A SWOT analysis identified key strengths (e.g., strategic partnerships, contextual adaptation), challenges (e.g., market demand, digital access), and opportunities for scaling. The report outlines a roadmap for contextualizing content, piloting the course, and building a sustainable digital learning offer to expand climate literacy among agricultural stakeholders in Senegal.